CASE SERIES: CHALLENGES AND OUTCOMES OF TLIF PROCEDURES IN A PERIPHERAL HOSPITAL IN BHARATPUR, RAJASTHAN - BANSAL, PUNEET; JOSHI, SHIFALI; INDOLIYA, RAJ KUMAR (International Journal of Current Pharmaceutical Research, 2024)
Objective: Chronic back pain, particularly from degenerative spinal conditions, significantly impacts patient quality of life, especially in regions with limited healthcare resources, such as rural Rajasthan. Transforaminal Lumbar Interbody Fusion (TLIF) has been recognized for its efficacy in treating severe spinal degeneration and instability. This case series examines the application of TLIF in a peripheral hospital setting, assessing its challenges and outcomes in such environments. Methods: This study included three patients aged 34 to 75, who underwent TLIF at a peripheral hospital in Bharatpur, Rajasthan, from February to July 2024. Detailed preoperative and postoperative evaluations were conducted, focusing on pain levels and functional mobility. Follow-ups were performed at the first, second, and fourth weeks post-surgery to monitor recovery and assess surgical success. Results: All patients reported significant improvements in pain and mobility by the first-month follow-up. The 34 y old female experienced complete pain relief and returned to full activities by four weeks. The 75 y old female and 65 y old male also showed considerable improvements in pain and function, with no severe complications noted during or after surgery. Conclusion: TLIF can be effectively implemented in peripheral hospital settings with outcomes comparable to those in higher-resource environments. This case series demonstrates the feasibility and significant benefits of advanced spinal surgeries in resource-limited settings, highlighting the potential for expanding such sophisticated interventions to improve healthcare accessibility and patient outcomes in rural areas.